Nematode-Associated Bacteria: Production of Antimicrobial Agent as a Presumptive Nominee for Curing Endodontic Infections Caused by Enterococcus faecalis - Donmez Ozkan, Hicran; Cimen, Harun; Ulug, Derya; Wenski, Sebastian; Yigit Ozer, Senem; Telli, Murat; Aydin, Neriman; Bode, Helge B.; Hazir, Selcuk (Frontiers in Microbiology, 2019)
Xenorhabdus and/or Photorhabdus bacteria produce antibacterial metabolites to protect insect cadavers against food competitors allowing them to survive in nature with their nematode host. The effects of culture supernatant produced by Xenorhabdus and Photorhabdus spp. were investigated against the multidrug-resistant dental root canal pathogen Enterococcus faecalis. The efficacy of seven different cell-free supernatants of Xenorhabdus and Photorhabdus species against E. faecalis was assessed with overlay bioassay and serial dilution techniques. Additionally, time-dependent inactivation of supernatant was evaluated. Among the seven different bacterial species, X. cabanillasii produced the strongest antibacterial effects. Loss of bioactivity in a phosphopantetheinyl transferase-deficient mutant of X. cabanillasii indicated that this activity is likely based on non-ribosomal peptide synthetases (NRPSs) or polyketide synthases (PKSs). Subsequent in silico analysis revealed multiple possible biosynthetic gene clusters (BGCs) in the genome of X. cabanillasii including a BGC homologous to that of zeamine/fabclavine biosynthesis. Fabclavines are NRPS-derived hexapeptides, which are connected by PKS-derived malonate units to an unusual polyamine, also PKS-derived. Due to the known broad-spectrum bioactivity of the fabclavines, we generated a promoter exchange mutant in front of the fabclavine-like BGC. This leads to over-expression by induction or a knock-out by non-induction which resulted in a bioactive and non-bioactive mutant. Furthermore, MS and MS2 experiments confirmed that X. cabanillasii produces the same derivatives as X. budapestensis. The medicament potential of 10-fold concentrated supernatant of induced fcl promoter exchanged X. cabanillasii was also assessed in dental root canals. Calcium hydroxide paste, or chlorhexidine gel, or fabclavine-rich supernatant was applied to root canals. Fabclavine-rich supernatant exhibited the highest inactivation efficacy of ≥3 log10 steps CFU reduction, followed by calcium hydroxide paste (≤2 log10 step). The mean percentage of E. faecalis-free dental root canals after treatment was 63.6, 45.5, and 18.2% for fabclavine, calcium hydroxide, and chlorhexidine, respectively. Fabclavine in liquid form or preferably as a paste or gel formulation is a promising alternative intracanal medicament.